Inheritance Law Reform, Empowerment, and Human Capital Accumulation : Second-Generation Effects from India - Deininger, Klaus (World Bank Group, Washington, DC, 2014)
This paper uses evidence from three Indian states, one of which amended inheritance legislation in 1994, to assess first- and second-generation effects of inheritance reform using a triple-difference strategy. Second-generation effects on education, time use, and health are larger and more significant than first-generation effects even controlling for mothers' endowments. Improved access to bank accounts and sanitation as well as lower fertility in the parent generation suggest that inheritance reform empowered females in a sustainable way, a notion supported by significantly higher female survival rates.